A Paradigm Revolution or Just Better Resolution-Will Newly Emerging Superresolution Techniques Identify Chromatin Architecture as a Key Factor in Radiation-Induced DNA Damage and Repair Regulation? - Falk, Martin; Hausmann, Michael (Cancers, 2020)
DNA double-strand breaks (DSBs) have been recognized as the most serious lesions in irradiated cells. While several biochemical pathways capable of repairing these lesions have been identified, the mechanisms by which cells select a specific pathway for activation at a given DSB site remain poorly understood. Our knowledge of DSB induction and repair has increased dramatically since the discovery of ionizing radiation-induced foci (IRIFs), initiating the possibility of spatiotemporally monitoring the assembly and disassembly of repair complexes in single cells. IRIF exploration revealed that all post-irradiation processes-DSB formation, repair and misrepair-are strongly dependent on the characteristics of DSB damage and the microarchitecture of the whole affected chromatin domain in addition to the cell status. The microscale features of IRIFs, such as their morphology, mobility, spatiotemporal distribution, and persistence kinetics, have been linked to repair mechanisms. However, the influence of various biochemical and structural factors and their specific combinations on IRIF architecture remains unknown, as does the hierarchy of these factors in the decision-making process for a particular repair mechanism at each individual DSB site. New insights into the relationship between the physical properties of the incident radiation, chromatin architecture, IRIF architecture, and DSB repair mechanisms and repair efficiency are expected from recent developments in optical superresolution microscopy (nanoscopy) techniques that have shifted our ability to analyze chromatin and IRIF architectures towards the nanoscale. In the present review, we discuss this relationship, attempt to correlate still rather isolated nanoscale studies with already better-understood aspects of DSB repair at the microscale, and consider whether newly emerging "correlated multiscale structuromics" can revolutionarily enhance our knowledge in this field.
Keywords: single-molecule localization microscopy (SMLM); DNA double-strand breaks (DSBs); linear energy transfer (LET); chromatin architecture; ionizing radiation-induced foci (IRIFs); superresolution microscopy; DSB repair pathway choice and hierarchy; DNA damage and repair; ionizing radiation